2010
DOI: 10.1002/anie.201003813
|View full text |Cite
|
Sign up to set email alerts
|

Diastereoselective Synthesis of Homoallylic Alcohols with Adjacent Tertiary and Quaternary Centers by Using Functionalized Allylic Aluminum Reagents

Abstract: Al be there for you: Sensitive functional groups, including ester and cyano groups, can be present in allylic aluminum reagents prepared by aluminum insertion in the presence of InCl3. These aluminum organometallic compounds undergo addition reactions to various functionalized aldehydes or ketones with remarkable diastereoselectivities allowing the construction of two adjacent quaternary and tertiary centers (see scheme).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…In comparison, except indium metal which mediated the reaction in 79% NMR yield with relatively good diastereoselectivity (entry 2), the use of other metals mostly led to poor product yields (entries 3–10). Although Knochel and co‐workers have reported that pre‐prepared cyclic allylic aluminium or zinc reagents could efficiently react with carbonyl compounds to afford the corresponding homoallylic alcohols with excellent diastereoselectivity, Al and Zn powder almost failed to promote the allylation reaction under optimized reaction conditions. Encouraged by the above results, subsequently we continued our task to explore the substrate scope of the reactions by using various aldehydes and cyclic allylic halides as substrates.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In comparison, except indium metal which mediated the reaction in 79% NMR yield with relatively good diastereoselectivity (entry 2), the use of other metals mostly led to poor product yields (entries 3–10). Although Knochel and co‐workers have reported that pre‐prepared cyclic allylic aluminium or zinc reagents could efficiently react with carbonyl compounds to afford the corresponding homoallylic alcohols with excellent diastereoselectivity, Al and Zn powder almost failed to promote the allylation reaction under optimized reaction conditions. Encouraged by the above results, subsequently we continued our task to explore the substrate scope of the reactions by using various aldehydes and cyclic allylic halides as substrates.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, when biphenyl 1 q containing both formyl and acetyl substituents were treated with cyclic allylic bromide 2 a in the presence of bismuth and LiI under the well‐established reaction conditions, the reaction took place regioselectively at the formyl group, leading to the expected product 3 u in 96% yield with >99:1 dr (Scheme ). The reluctancy of acetyl group to participate in the allylation reaction clearly indicated that the in situ formed allylic bismuth reagent was a mild organometallic reagent, when compared to its allylic aluminium or zinc counterparts which might react with both aldehyde and ketone without regioselectivity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, achieving such a level of selectivity with ketones is rare 12. Recently, the highly diastereoselective addition of cyclic allylalanes onto methylketones was described 4a. We thus decided to investigate ketones in our catalytic conditions (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…We further studied the influenceo ft he aryl group next to the CF 3 group on the reactivity.B enzofulvenes 1b-d with a p-Cl or p-methyl substituted phenylg roup or at hiophener ing afforded the expectedp roducts 4p-r in good to excellent yields upon reaction with p-bromobenzaldehyde 3a under standardc onditions (entries [17][18][19]. In contrast, no CÀFa ctivation reaction was observed in the case of the strongly electron-donatingN Me 2 group at the para position of benzofulvene 1e (entry 20).…”
Section: Entrymentioning
confidence: 99%